2012
DOI: 10.1080/17429145.2011.619281
|View full text |Cite
|
Sign up to set email alerts
|

Triacontanol: a potent plant growth regulator in agriculture

Abstract: Triacontanol (TRIA) is a natural plant growth regulator found in epicuticular waxes. It is used to enhance the crop production in millions of hectares, particularly in Asia. Quite a number of researchers have reported the TRIA-mediated improvement in growth, yield, photosynthesis, protein synthesis, uptake of water and nutrients, nitrogen-fixation, enzymes activities and contents of free amino acids, reducing sugars, soluble protein, and active constituents of essential oil in various crops. Expectedly, TRIA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 74 publications
(146 reference statements)
0
70
0
Order By: Relevance
“…Dobránszki and Teixeira da Silva (2010) stated that the success in apple in vitro culture is affected by many factors, including genotype and physiological state of the donor plant, and in vitro conditions (e.g., culture media composition, temperature and light). Studied in our experiment bio-stimulant triacontanol (TRIA) have been identified as natural plant growth regulator that enhances crop production due to involving in several physiological pathways (Naeem et al 2012). It was reported as a factor increasing dry weight of corn seeds, leaf area of rice, promotion of tobacco callus, stimulation of shoot growth, induction of early flowering, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Dobránszki and Teixeira da Silva (2010) stated that the success in apple in vitro culture is affected by many factors, including genotype and physiological state of the donor plant, and in vitro conditions (e.g., culture media composition, temperature and light). Studied in our experiment bio-stimulant triacontanol (TRIA) have been identified as natural plant growth regulator that enhances crop production due to involving in several physiological pathways (Naeem et al 2012). It was reported as a factor increasing dry weight of corn seeds, leaf area of rice, promotion of tobacco callus, stimulation of shoot growth, induction of early flowering, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Triacontanol (TRIA) is a potent plant growth regulator, which has been reported to enhance growth and yield of several crop species when applied exogenously (Gatica et al 2008;Naeem et al 2011). TRIA has been reported to enhance photosynthesis and water and mineral nutrients' uptake, regulate activities of various enzymes and increase the level of various organic compounds in leaf tissues (Ries & Houtz 1983;Ries 1991;Naeem et al 2009Naeem et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that triacontanol given on the optimum concentration will promote the expression of genes, so that it will activate a particular gene to control the process of organogenesis to initiate a shoot and root of the growth of cacao seedlings. Naeem et al (2012) also reported that triacontanol possible role in regulating growth and metabolism of plants lies in the regulation of gene expression. According to Hangarter and Ries (1978) triacontanol potentially increases growth due to the increase in the number of cells in the plant.…”
Section: Discussionmentioning
confidence: 99%